Severe Life Threatening Maxillofacial Infection in Pregnancy Presented as Ludwig's Angina - Shelly Abramowicz; Jacques S. Abramowicz; M. Franklin Dolwick (Hindawi Limited, 2006)
Background. Ludwig's angina is a rapidly spreading cellulitis that may produce upper airway obstruction often leading to death. There is very little published information regarding this condition in the pregnant patient. Case. A 24-year old black female was admitted at 26 weeks gestation with tooth pain, submandibular swelling, severe trismus, and dysphagea, consistent with Ludwig's angina. Her treatment included emergent tracheostomy, incision and drainage of associated spaces, teeth extraction, and antibiotic therapy. Conclusions. During a life threatening infectious situation such as the one described, risks of maternal and fetal morbidity include both septicemia and asphyxia. Furthermore, the healthcare provider must consider the risks that the condition and the possible treatments may cause the mother and her unborn child.